2015
DOI: 10.1002/2014jc010461
|View full text |Cite
|
Sign up to set email alerts
|

A neural network‐based four‐band model for estimating the total absorption coefficients from the global oceanic and coastal waters

Abstract: In this study, a neural network-based four-band model (NNFM) for the global oceanic and coastal waters has been developed in order to retrieve the total absorption coefficients a(k). The applicability of the quasi-analytical algorithm (QAA) and NNFM models is evaluated by five independent data sets. Based on the comparison of a(k) predicted by these two models with the field measurements taken from the global oceanic and coastal waters, it was found that both the QAA and NNFM models had good performances in de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…[] showed that the performance of the QAA algorithm is strongly dependent on the retrieval uncertainty of the total absorption coefficient at the reference band, but a simple empirical approach was applied for deriving this total absorption coefficient in the QAA algorithm. In fact, this empirical method could suppress some effects of backscattering signals, rather than removing them completely [ Chen et al ., ]. Consequently, the strong backscattering signals in the turbid coastal waters inevitably resulted in the large uncertainty present in the total absorption coefficient estimations [ Chen et al ., ], and then affected the QAAG results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[] showed that the performance of the QAA algorithm is strongly dependent on the retrieval uncertainty of the total absorption coefficient at the reference band, but a simple empirical approach was applied for deriving this total absorption coefficient in the QAA algorithm. In fact, this empirical method could suppress some effects of backscattering signals, rather than removing them completely [ Chen et al ., ]. Consequently, the strong backscattering signals in the turbid coastal waters inevitably resulted in the large uncertainty present in the total absorption coefficient estimations [ Chen et al ., ], and then affected the QAAG results.…”
Section: Resultsmentioning
confidence: 99%
“…Note that the points at the high end were mainly taken from the turbid coastal zones where the backscattering signals were very strong. Chen et al [2015] showed that the performance of the QAA algorithm is strongly dependent on the retrieval uncertainty of the total absorption coefficient at the reference band, but a simple empirical approach was applied for deriving this total absorption coefficient in the QAA algorithm. In fact, this empirical method could suppress some effects of backscattering signals, rather than removing them completely [Chen et al, 2015].…”
Section: Test With the Global In Situ Data Setmentioning
confidence: 99%
“…The R rs spectra were synthesized with a database of inherent optical properties (IOP) presented in the International Ocean Color Coordinating Group report [ IOCCG , ]. The synthetic IOP data cover a wide range of aquatic environments and have been extensively used for model development and validation [ Chen et al ., ; Salama and Stein , ; Wang et al ., ; Wei and Lee , ; Wei et al ., ]. The remote‐sensing reflectance was simulated by Hydrolight 5.1 [ Mobley and Sundman , ].…”
Section: Evaluation Of the Qa Systemmentioning
confidence: 99%
“…For example, the widely used band ratio [O'Reilly et al, 1998] or band difference [Hu et al, 2012] algorithms for [CHL] rely on R rs data at both blue and green wavelengths. Semianalytical bio-optical algorithms require the R rs spectrum at more wavelengths as inputs [Ciotti et al, 1999;IOCCG, 2000IOCCG, , 2006. Thus, the QA of every individual R rs spectrum is fundamental for accurate remote sensing of water-column properties.…”
Section: Bio-optical Implications and Significancementioning
confidence: 99%
“…However, the retrieval accuracy of SAKM model strongly depends on the estimation accuracy of quasi-analytical model (QAA)-derived a ( λ ) and b b ( λ ) [ 8 ]. Actually, the QAA model is able to suppress the effect of total backscattering coefficient, b b ( λ ), instead of eradicating it completely [ 14 ], which in turn lead to the violation of QAA model in turbid coastal waters. Moreover, Wang et al [ 10 ] and Chen et al [ 11 ] also suggested that some problems may be encountered, when the SAKM model is used to derive K d ( λ ) from turbid coastal waters.…”
Section: Introductionmentioning
confidence: 99%